2014
DOI: 10.1002/ldr.2292
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Sodic Soil for Wheat Cultivation Using Bioaugmented Organic Soil Amendment

Abstract: A novel bioaugmented organic amendment (SF OA ) [consisted of vermicompost (pre-enriched with plant growth promoting fungi) mixed with pressmud and Azadirachta indica (A. Juss.) seed cake] was developed to reclaim sodic soil and support wheat production. A field trial of the SF OA application with/without chemical fertilizers conducted in completely randomized design with four replications to compare growth, yield and seed protein contents of wheat (Triticum aestivum L.) on sodic soil. The favourable changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…The Haplic Luvisol showed increases in pH and CEC with biochar application (Table ), so P desorption may have been responsible for increasing P solubility (e.g., H 2 O‐P i ) in the soils (Jiang, Yuan, Xu, & Bish, ). Third, biochar application changed the form of Fe, Al, Ca, and other agents of P adsorption (fixation), all of which significantly influenced soil P transformation (Parvage, Ulén, Eriksson, Strock, & Kirchmann, ; Srivastava, Gupta, Shikha, & Tewari, ; Xu, Wei, Sun, Shao, & Chang, ). However, the previous studies indicated that biochar containing moderate Ca 2+ and Mg 2+ formed precipitates with phosphate in the soils and increases the phosphorus adsorption (Jiang, Yuan, Xu, & Bish, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Haplic Luvisol showed increases in pH and CEC with biochar application (Table ), so P desorption may have been responsible for increasing P solubility (e.g., H 2 O‐P i ) in the soils (Jiang, Yuan, Xu, & Bish, ). Third, biochar application changed the form of Fe, Al, Ca, and other agents of P adsorption (fixation), all of which significantly influenced soil P transformation (Parvage, Ulén, Eriksson, Strock, & Kirchmann, ; Srivastava, Gupta, Shikha, & Tewari, ; Xu, Wei, Sun, Shao, & Chang, ). However, the previous studies indicated that biochar containing moderate Ca 2+ and Mg 2+ formed precipitates with phosphate in the soils and increases the phosphorus adsorption (Jiang, Yuan, Xu, & Bish, ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil salinization and alkalization are serious soil degradation problems worldwide, encroaching on limited arable land and causing decrease in agricultural yields in many arid and semiarid regions. This poses a severe challenge to the sustainable development of agriculture (Qadir et al, ; Shaygan, Reading, & Baumgartl, ; Srivastava, Gupta, Shikha, & Tewari, ). Because saline–alkali land is usually flat and easy to cultivate with a deep soil layer, the improvement of saline–alkali land can effectively increase the area of cultivated land to enhance agricultural productivity and food security (Chi, Zhao, Sun, & Wang, ; Qadir, Noble, & Chartres, ; Rasouli, Kiani Pouya, & Karimian, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, numerous studies have indicated that restoration needs to recover soil functionality, and this call is taking place all over the world (Ahmad et al, 2013;Johnston et al, 2013;Mao et al, 2014;Moreno et al, 2014;Novara et al, 2014;Roy and McDonald, 2015;Sacristán et al, 2015;Sadeghi et al, 2015;Srivastava et al, 2014). Some authors indicate that this task should be accomplished with a broad view by considering how soils can interfere with human health (Brevik and Sauer, 2015).…”
Section: N Seco-reigosa Et Al: Adsorption Desorption and Fractionamentioning
confidence: 99%